PENGARUH PERTUMBUHAN PENJUALAN, RETURN ON ASSET DAN DEBT TO EQUITY RATIO TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016-2018 - Trisna Novela Sari; Rahmawati Rahmawati (Jurnal Riset Manajemen Indonesia, 2020)
This research was conducted with the aim to examine the effect of sales growth, ROA, and DER and variables that affect the value of the company in the textile and garment sub-sector companies listed on the Indonesia stock exchange in 2016-2018. The population in this study were all textile and garment sub-sector companies listed on the Indonesia stock exchange in the 2016-2018 period. The technique used in sampling is purposive sampling method, the samples in this study were selected as many as 11 companies. Hypothesis testing uses multiple linear regression analysis with the help of SPSS 23.00 for windows. The results showed that simultaneous sales growth, ROA, and DER affect the value of the company. Partially, DER has an effect on firm value.